Analysis of cross neutralizing activity of antibodies from sera of severe fever with thrombocytopenia syndrome patients to deal with different genotype strains - Xu, Jiaxin; Liu, Yuanni; Zhang, Fan; Wang, Xin; Huang, Weijin; Wu, Yulong; Li, Boqing; Zhuang, Jiapeng; Bing, Yixing; Wang, Youchun; Qiao, Yuanyuan (Frontiers in Microbiology, 2022)
Background: Severe fever with thrombocytopenia syndrome bunyavirus (SFTSV) is a tick-borne virus that causes severe communicable fever with thrombocytopenia syndrome (SFTS) with an average case fatality rate of 10%. In the study, we aimed to identify the cross-neutralizing antibody (nAb) against different genotype strains from sera of SFTSV infected patients. Methods: Firstly the serotype of SFTSV was identified by constructing a phylogenetic tree based on the M segments epidemic in the Jiaodong area of Shandong province, then different sera of subject cross reactive with recombinant Gn-Fc (rGn) of 0921 strain were examined. The levels of polyclonal nAbs from sera of 25 convalescents were measured by a pseudovirus-based neutralizing experiment. Results: We found local endemic strains were mainly C2 and C3 isolates of SFTSV. 14 of 15 sera from donors were binding with 0921 rGn. Cross nAbs were produced by 10 of 25 sera from donors during the period of 2019–2021. Among these, five nAbs (A2, A4, A5, L9, and L10) neutralized the pseudoviruses of HB29, Gangwon, HN13, HN20, SPL030A, and SD4 strains. Conclusion: Our data suggested that epidemic strains showed relatively stable heredity. Some blood sources from patients produced cross nAbs that could neutralize all of the strains examined. These findings highlight the important role played by humoral immunity in combatting SFTSV.